Transformasi Pencegahan Bullying Menuju Sekolah Ramah Anak Berbasis Society 5.0 di SDN Teluklada 2 - Hidayat, Amat; Asqoliyah, Asqoliyah; Mutoharoh, Mutoharoh; Jalaludin, Muhammad; Andhini, Desti Tri; Nuraida, Putri; Sulastri, Sulastri; Sayyidati, Sayyidati; Adzkiatunnissa, Fathia; Rivanty, Delia (Universitas Pahlawan Tuanku Tambusai, 2025)
Bullying remains a serious challenge in elementary schools, with negative impacts on children’s psychological, social, and academic development. This study aims to describe the transformation of bullying prevention toward a child-friendly school based on Society 5.0 at SDN Teluklada 2, Sobang District, Pandeglang Regency. The activity was carried out during the Community Service Program period (July 8–August 23, 2025), involving all 4th–6th grade students and teachers. The methods used were socialization and education focusing on the definition, types, and impacts of bullying. Educational activities utilized interactive digital media, group discussions, and role-play simulations to encourage active student participation. The results showed a significant improvement in students’ understanding of the dangers of bullying, increased willingness to report incidents, and the growth of empathy toward peers. Teachers played an active role as facilitators, supervisors, and role models by implementing technology-based learning aligned with the principles of Society 5.0. The program’s impact was evident in the creation of a more conducive, safe, and child-friendly school environment. The application of Society 5.0 proved effective in supporting preventive efforts against bullying while fostering a collective awareness among the entire school community to maintain a healthy and inclusive educational environment.